2015
DOI: 10.1002/j.0022-0337.2015.79.2.tb05865.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Professional Development Needs of Educators in the Health Sciences Professions

Abstract: An increasing number of institutions of higher education are clustering their health sciences schools into a common unit. Therefore, it is imperative that the individual faculty development units assume new mandates to meet faculty development needs for stakeholders across these disciplines. Critical to providing current and relevant professional development activities is an awareness of the needs of academicians, including common as well as discipline-speciic needs. Hence, the aim of this study was to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
0
25
0
2
Order By: Relevance
“…The purpose and scope of needs assessment must be guided by a clear conceptual framework, the purpose and scope of prospective FD programs, and institutional strategies and resources. 2,16 Exploratory interviews during developing the survey in this study revealed that medical faculty at Sohag University conceptualize discipline-specific development as an essential part of FD construct. This area has commonly been overlooked in the literature on FD and its needs assessment with the notion that faculty are usually hired based on their discipline (content) expertise; hence, FD should focus on other areas.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The purpose and scope of needs assessment must be guided by a clear conceptual framework, the purpose and scope of prospective FD programs, and institutional strategies and resources. 2,16 Exploratory interviews during developing the survey in this study revealed that medical faculty at Sohag University conceptualize discipline-specific development as an essential part of FD construct. This area has commonly been overlooked in the literature on FD and its needs assessment with the notion that faculty are usually hired based on their discipline (content) expertise; hence, FD should focus on other areas.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, most published FD studies addressed teaching, research, and leadership/administration aspects. 8,[15][16][17][18][19][20][21][22] However, the essence of FD is continually supporting all roles of faculty members dedicated to meeting the goals, mission, and vision of the institution. 3 Teaching, research, and social service (including healthcare), which form the core mission of any medical school, require discipline (content) expertise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Items used in each scale are provided in Data or upon request from the primary author.) The items were based on similar items used in surveys published in the literature . Participants rated statements on a 6‐point Likert scale (1 = ‘strongly disagree’, 2 = ‘disagree’, 3 = ‘somewhat disagree’, 4 = ‘somewhat agree’, 5 = ‘agree’, and 6 = ‘strongly agree’), but participants were also given the option of ‘choose not to answer’.…”
Section: Methodsmentioning
confidence: 99%